English Language Learners’ Perception and Motivation Towards Exam Format: A Qualitative Study - Griche, Salmane (International Journal of Language and Literary Studies, 2024)
The objective of this study is to explore the perceptions of students at the English department at Ibn Tofail University towards exam format, and the motivation behind their preferences. In order to achieve these objectives, a qualitative methodology was employed. The subjects of this study are sixteen undergraduate students currently enrolled at the English department at ITU, and three students who recently graduated from the same university. An open-ended questionnaire is used to glean the necessary information, and to allow the subjects to freely express their opinions and attitudes with minimal influence. The collected data is analyzed using thematic analysis. Findings show that ITU’s EFL students believe that MCQ exams cannot properly assess writing skills, or competency in certain courses. The MCQ exam preference is mainly motivated by the practicality of the format, while the written format preference is mainly motivated by the fact that it encourages deep learning, enables higher cognitive levels of thinking, and improves writing skills.